From The History Of The Population Census In Uzbekistan - Yusupov Rahimjon Karimovich (Peerian Journals Publishing, 2024)
When studying the state of demographic processes in Uzbekistan, data from the population census, which will be conducted for the first time in the years of independence of the country, are of great importance. For the first time, the history of the population census in Uzbekistan is studied, scientific methods of historical demography are used, and the modern processes of official population censuses are also revealed. The population census in Uzbekistan is considered an event of national significance. The participation of the people of the republic in this event is considered a necessary condition for democracy.
Keywords: census; population; program; every five or ten years